USE OF MOBILE EDUCATIONAL TECHNOLOGIES IN TEACHING THE SUBJECT OF INFORMATION AND INFORMATION TECHNOLOGIES - Mamasoliyev Akmaljon Azizjon oglu (The Conference Hub, 2025)
This article discusses the theoretical foundations and practical significance of using mobile educational technologies in the process of teaching the subject "Informatics and Information Technologies". The possibilities of developing students' interest in independent learning and digital competencies using mobile applications, online platforms and digital learning resources are analyzed. The advantages of mobile education, mechanisms for integrating it into the educational process, methodological approaches of teachers and recommendations for increasing efficiency are also given. The results of the study show that mobile educational technologies can enhance interactivity in computer science lessons, individualize the learning process and increase the level of students' knowledge acquisition.
Keywords: mobile education, digital technologies, computer science education, mobile applications, information technologies, electronic resources, interactive learning, digital competence, learning process, distance learning.